Deterioration of our native pasture-lands and their remedies - Buell, Thomas Warner (My University, 1904)
Introduction: The range of the future will either be occupied by the owner or be under his supervision. It will thus be well handled and instead of being simply a semi wilderness will be the seat of homes and settled life. The ranches will be smaller and more numerous. Better grades of stock will be kept with these conditions we may expect our range country- The Great Plains- to be one of the richest and most pleasant portions of our great republic.
Citation: Buell, Thomas Warner. Deterioration of our native pasture-lands and their remedies. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: The Great Plains; Geography; North America; Geology; Environmental Issues; Theses; Manuscripts (documents)